Assessment of Awareness About COVID-19 Infection among Medical Personnel and General Public of Rahim Yar Khan - Hafiz Muhammad Hashaam Tahir, Muhammad Maaz Saleem, Aansa Komal, Adan Javaid Khokhar, Muhammad Imran Yaseen, Mariya Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Assessment of awareness about COVID-19 among medical personnel and general public. Study Description: It is a Cross-Sectional study carried out in R.Y.Khan from June 2020 to September 2020. Methodology: About 430 subjects (medical personnel and general public) were asked to fill a pre-designed questionnaire by using convenient sampling technique. The questionnaire included information regarding their bio-data and study questions. Then SPSS Version 21 was used for data analysis. Results: Our study shows that 90.5% study subjects think that they are well aware about COVID-19 while 9.5% subjects think that they aren’t. In response to question “Is it lethal?” 25.3% subjects replied Always, 67% said Sometimes and 7.7% said Never. 68.6% subjects said that it is Always transmissible, 15.8% said Sometimes and 15.6% said Never. Regarding modes of its spread, 76.5% subjects agreed to Cough, 67.9% to Handshake, 27.9% to Food-sharing, 35.6% to Room-sharing, 28.6% to Utensils-sharing, 21.2% to Fomites-sharing. 6.7% subjects said that its vaccine is Available, 72.1% replied as Not-Available and 21.2% said that they don’t know. 24.9% subjects said that its specific treatment is Available, 53.3% replied as Not-Available and 21.9% said that they don’t know. 71.9% subjects said that it is preventable by adopting specific preventive measures, 8.8% said it isn’t and 19.3% said that they don’t know. Regarding effectiveness of PPEs as preventive measures, 85.8% subjects agreed to Mask, 57.2% to Gown, 52.3% to Goggles, 45.6% to Head-cover, 35.1% to Shoe-cover, 55.8% to Gloves, 70.7% to Social-distancing, 58.4% to use of Hand-wash/Hand-Sanitizer. Conclusion: There is observed some lack of knowledge in different areas regarding COVID-19, almost equally, among medical personnel as well as among general public that results in spread of infection at exponential rates due to negligence of people including poor understanding and poor compliance to the preventive measures advised by health authorities worldwide.